Curators of Global Buddhism: A Critical Genealogy and Decolonial Reading of Contemporary Curatorial Practices in Buddhist Studies - Eaghll, Tenzan (Method & theory in the study of religion, 2024)
This article offers the first critical genealogy of scholarship on the category of “global Buddhism” and its related literature. The category was first theorized around the turn of the millennium and has since been used in multiple publications, yet in all this scholarship, there is no clear definition, classification, or critical evaluation of the term. This article, therefore, details the different histories, taxonomies, and examples associated with global Buddhism, the relationship between power and knowledge in such representations, and clarifies what, if anything, any of this has to do with the category of “religion,” a question whose critical dimensions have been ignored by scholars on the topic thus far. Since the category rose to prominence alongside a series of others like “Buddhist Modernism,” “postmodern Buddhism,” and “global religion,” the article also draws attention to the curatorial practices that inform the academic study of Buddhism and religion and critiques the remnants of colonialism, orientalism, and universalism still operative in late capitalist scholarship. Theoretically, the article is informed by critical theory from the study of religion and Decolonial thought. Overall, it suggests deep ties between global Buddhism and what Anibal Quijano calls the coloniality of power but also suggests critical ways to employ the category going forward.